Participation, Learning, and Identity: Dialectical Perspectives - Roth, Wolfgang M; Hwang, SungWon; Goulart, Maria I; Lee, Yew Jin (Lehmanns Media, 2016)
Over the past two decades, western scholars increasingly have embraced cultural-historical activity theory as a framework for thinking about knowing and learning in school and workplace settings. Yet in the adoption of this framework, many of its fundamental underpinnings in materialist dialectic have dis-appeared. Cultural-historical activity theory has been fitted to a fundamentally dualistic way of thinking the subject and object of activity, individual and collective, subjectivity and intersubjectivity, abstract and concrete, etc.This book redresses the inappropriate translation by radically sticking to a materialist-dialectical theorizing of knowing, learning, participation, and identity. The authors draw on several detailed ethnographic studies at the kindergarten, elementary school, and middle school levels and in a workplace as case materials to articulate various aspects of the specifically human activity observed in each setting.Wolff-Michael Roth is Lansdowne Professor of applied cognitive science at the University of Victoria (UVic) and director of the CHAT@UVic laboratory concerned with the investigation of knowing and learning in science and mathematics across the lifespan. SungWon Hwang is postdoctoral fellow at UVic studying embodied cognition. Yew Jin Lee is a Ph.D. candidate at UVic focusing on workplace learning. Maria Inês Mafra Goulart is a Ph.D. candidate investigating science learning in kindergarten schools.